Genome-Wide Identification and Salt Stress-Responsive Expression Analysis of the GmPLATZ Gene Family in Soybean (Glycine max L.) - Mingyu Wang; Zheyun Guan; Songquan Wu; Jingyong Zhang; Chunjing Lin; Yanyan Sun; Mingzhe Shen; Chunbao Zhang (Plants, 2025)
The plant-specific PLATZ transcription factors play crucial roles in plant growth, development, and responses to abiotic stresses. However, despite their functional significance, PLATZ genes remain poorly characterized in soybeans. In this study, we conducted a genome-wide analysis of the GmPLATZ gene family and investigated their expression profiles under salt stress. We identified a total of 29 GmPLATZ genes in the soybean genome and systematically analyzed their physicochemical properties, conserved domains, evolutionary relationships, cis-acting elements, and expression regulation patterns. Subcellular localization predictions indicated nuclear localization for most GmPLATZs, except for GmPLATZ5 and GmPLATZ14, which showed dual chloroplast–nuclear localization. A gene family expansion analysis indicated that 21 segmental duplication events were the primary driver of GmPLATZ diversification. A phylogenetic analysis classified the GmPLATZ genes into four subgroups, while gene structure and motif analyses revealed conserved zinc-binding domains and identified multiple cis-acting elements associated with light responsiveness, hormone signaling, and stress responses. Expression profiling showed tissue-specific expression patterns, with 13 GmPLATZ genes differentially expressed under salt stress, including root-preferential members (e.g., GmPLATZ1, GmPLATZ10) and leaf-preferential members (e.g., GmPLATZ8, GmPLATZ9). This study provides a theoretical basis for further investigation of GmPLATZ gene functions in soybean development and stress tolerance.